Aspectos processuais da alienação fiduciária de bens móveis e imóveis - Ávila, Henrique (2014)
The paper analyzes fiduciary alienation in Brazilian law and its mechanisms of enforcement at the disposal of the parties that conclude this type of contract. After passing through the definitions of fiduciary business, fiduciary property, and fiduciary alienation, the paper presents the current panorama of Brazilian legislation on the issue, briefly enunciating the statutes in effect and the type of fiduciary alienation each one of them covers. In the third and fourth chapters, one describes the possible reliefs to enforce the guarantee of movable assets and real property, whether judicial or extra-judicial, by the fiduciary-creditor or even by the fiduciary-debtor, which can also resort to reliefs to protect itself from wrongful use by the creditor or third parties. These two chapters conclude with a description of the general panorama of these reliefs for the fiduciary alienation of immovable assets and real property. In the fifth chapter, the thesis deals with a few current issues in which consensus cannot be found among authorities or in case law, to which one aims to suggest solutions appropriate to positive law and to its regulating principles. In the sixth and final chapter, one points to the difficulties in the interpretation and application of the fiduciary business due to a lack of homogeneous regulation, specific to this doctrine. Finally, the thesis draws a conclusion about the application of the current norms and, lastly, suggests regulation for the doctrine